Antibody Levels Of Health Personnel Post-Booster Vaccination Phase-III - Nur Fajri; Muh. Nasrum Massi (JKM (Jurnal Kebidanan Malahayati), 2022)
ABSTRACK Background: Health workers are one of the groups most at risk of being infected with Covid-19 due to their intense interactions with patients. Therefore, it is necessary to make efforts to increase the endurance of the pandemic by administering vaccines.Purpose: This study aims to determine the effectiveness of giving phase III booster vaccinations for health workers against increasing Covid-19 antibody titers.Methode: This study belongs to the type of descriptive quantitative research, the sampling technique is carried out using the slovin formula.Results: The results showed that constantly (100%), giving booster vaccinations to health workers can increase the effectiveness of the Covid-19 vaccine that has previously been given and is able to strengthen the antibody that has been awakened.  Conclusion: The administration of the phase III booster vaccine can increase the titer of the Covid-19 antibody so that the risk of transmission of the corona virus can be suppressed.Suggestion: Other puskesmas can carry out phase-III booster vaccinations for health workers as a whole